Zinc-plated steel sheet
By controlling the internal oxidation and decarburization layers in zinc-based plated steel sheets, the issues of uneven alloying and strength reduction are addressed, achieving high-strength steel sheets with improved plating properties and appearance for automotive parts.
Patent Information
- Application Number
- JP2023520590
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-10
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2041-05-10
AI Technical Summary
High-strength steel sheets used in automobile parts face issues with insufficient plating properties and appearance due to the formation of external oxides and decarburization, which affect the mutual diffusion between steel and zinc-based plating components, leading to uneven alloying and strength reduction.
Control the ratio of internal oxidation layer thickness to decarburized layer thickness within specific ranges (A/B: 0.01 to 0.50 and B/t: 0.001 to 0.200) in zinc-based plated steel sheets with a thickness of 0.10 to 0.95 mm, ensuring both high strength and plating properties by forming an internal oxidation layer and minimizing decarburization.
The solution results in a zinc-based plated steel sheet with sufficient strength and excellent appearance properties, suitable for automotive applications, by preventing unplated areas and alloying unevenness while maintaining strength.
Smart Images

Figure 0007610161000005 
Figure 0007610161000006 
Figure 0007610161000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a zinc-based plated steel sheet. More specifically, the present invention relates to a zinc-based plated steel sheet that is thin and has high strength and has excellent appearance properties. [Background technology]
[0002] In recent years, efforts have been made to increase the strength of steel sheets used in various fields such as automobiles, home appliances, and building materials. For example, in the automobile field, the use of high-strength steel sheets has been increasing in order to reduce the weight of vehicle bodies in order to improve fuel efficiency. Such high-strength steel sheets typically contain elements such as C, Si, and Mn to improve the strength of the steel.
[0003] Among automotive components, components such as doors, bonnets, and roofs have a much larger area than frame components such as pillars, and therefore the high-strength steel sheets used for these components generally have a smaller thickness and a much larger width in order to reduce weight. Furthermore, such components account for a large portion of the exterior of an automobile, and therefore are required to have not only high strength but also excellent appearance.
[0004] On the other hand, particularly when used for automotive components, high-strength steel sheets are provided with a plating layer such as a hot-dip galvanized layer or a galvannealed hot-dip galvanized layer on the surface in order to improve corrosion resistance, etc. In general, before forming such a plating layer, the steel sheet (typically a cold-rolled steel sheet) is often annealed at a certain temperature or higher in order to remove distortion and / or improve workability of the steel sheet.
[0005] In this regard, hot-dip galvanized steel sheets or galvannealed steel sheets containing C, Si, Mn, etc. as steel sheet components and suitable for use mainly as automotive parts, and methods for producing the same have been disclosed (for example, Patent Documents 1 to 4). Patent Documents 1 to 4 also teach that, in order to produce the plated steel sheets described in Patent Documents 1 to 4, an annealing step is or may be performed before the plating step. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2014 / 054141 [Patent Document 2] JP 2014-058741 A [Patent Document 3] International Publication No. 2013 / 157222 [Patent Document 4] JP 2010-065269 A Summary of the Invention [Problem to be solved by the invention]
[0007] Among the elements typically contained in high-strength steel sheets, Si and Mn, which are elements with a strong affinity for oxygen, may combine with oxygen in the atmosphere during the annealing process to form a layer containing an oxide near the surface of the steel sheet. The form of such a layer can be exemplified by a form in which an oxide containing Si or Mn is formed as a film on the outside (surface) of the steel sheet (external oxidation) and a form in which an oxide is formed inside (surface layer) of the steel sheet (internal oxidation).
[0008] When a zinc-based plating layer (e.g., a hot-dip galvanized layer or an alloyed hot-dip galvanized layer) is formed on the surface of a steel sheet on which an outer oxide layer is formed, the oxides are present on the surface of the steel sheet as a film, and therefore the mutual diffusion between the steel components (e.g., Fe) and the plating components (e.g., Zn) is inhibited. As a result, the reaction between the steel and the plating layer is adversely affected, and the plating property may become insufficient (e.g., the number of unplated parts increases). This may result in deterioration of the appearance and rust prevention performance of the plated steel sheet. In addition, these oxides also affect the Fe-Zn reaction rate when alloying the plating layer, and as a result, the plating property may become insufficient (e.g., uneven alloying may occur). In such a case, the appearance of the plated steel sheet may also deteriorate. Therefore, from the viewpoint of improving the plating property and obtaining a plated steel sheet with good appearance, a steel sheet on which an inner oxide layer is formed, in which an oxide exists inside, is preferable to a steel sheet on which an outer oxide layer is formed.
[0009] On the other hand, under annealing conditions that form an internal oxide layer, not only is the internal oxide layer formed, but also the phenomenon of decarburization occurs near the surface of the steel sheet. Decarburization refers to the carbon near the surface of the steel sheet combining with oxygen in the annealing atmosphere to become CO2 and be released outside the system, and the area where carbon is insufficient is called the decarburized layer. Since carbon in steel is an element that contributes to the strength of the steel, the strength near the surface of the steel sheet decreases as the decarburized layer becomes thicker. When the thickness of the zinc-based plated steel sheet is thick, the decrease in strength of the steel sheet surface due to the presence of such a decarburized layer is not particularly problematic because its influence is relatively small. However, in the case of a zinc-based plated steel sheet with a very thin thickness, the influence of the decrease in strength due to this decarburization cannot be ignored.
[0010] In view of the above circumstances, an object of the present invention is to provide a zinc-based plated steel sheet having a thin sheet thickness that is capable of achieving both sufficient strength and galvanizability. [Means for solving the problem]
[0011] The present inventors have found that in a zinc-based plated steel sheet having a thickness of 0.10 to 0.95 mm, both high strength and high galvanizability can be achieved by strictly controlling the ratio of the thickness of the internal oxide layer on the surface of the steel sheet to the thickness of the decarburized layer, and the ratio of the thickness of the decarburized layer to the thickness of the steel sheet.
[0012] The present invention has been made based on the above findings, and the gist of the present invention is as follows. (1) In mass%, C: 0.05-0.30%, Si: 0.01 to 3.00%, Mn: 0.80-3.00%, Al: 0.010-2.000%, P: 0.100% or less, S: 0.100% or less, N: 0.0300% or less, O: 0.010% or less, B: 0~0.0100%, Ti: 0 to 0.100%, Nb: 0 to 0.100%, V: 0~0.10%, Cr: 0-1.00%, Ni: 0 to 0.10%, Cu: 0-0.10%, Mo: 0 to 0.50%, W: 0 to 0.50%, Ca: 0-0.100%, Mg: 0~0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0~0.100% and the balance being Fe and impurities, and the sheet thickness is 0.10 to 0.95 mm; and a zinc-based plating layer formed on at least one surface of the steel sheet, The tensile strength is 550 to 1500 MPa. When the thickness of the internal oxide layer on one side of the steel plate is A (μm), the thickness of the decarburized layer on one side of the steel plate is B (μm), and the plate thickness of the steel plate is t (μm), A / B: 0.01 to 0.50; B / t: 0.001~0.200, zinc-based coated steel sheet. (2) When the sheet width of the steel sheet is 1500 to 3000 mm, the standard deviation in the width direction of the thickness of the internal oxide layer is a (μm) and the standard deviation in the width direction of the thickness of the decarburized layer is b (μm), A: 1.0 μm or more, B: 10 μm or more, a / A: 0.15 or less, The zinc-based plated steel sheet according to (1), wherein b / B is 0.20 or less. (3) The zinc-based plated steel sheet according to (1) or (2), wherein, in mass%, Si+Mn: 5.00% or less, and Si / Mn: 1.50 or less. (4) The steel plate comprises, in mass%, B: 0.0001~0.0100%, Ti: 0.001 to 0.100%, Nb: 0.001 to 0.100%, Cr: 0.01 to 1.00%, Mo: 0.01 to 0.50%, and W: 0.01 to 0.50% The zinc-based plated steel sheet according to any one of (1) to (3), having a component composition containing one or more of the above. (5) The steel plate comprises, in mass%, V: 0.01 to 0.10%, Ni: 0.01 to 0.10%, Cu: 0.01 to 0.10%, Ca: 0.001 to 0.100%, Mg: 0.001 to 0.100%, Zr: 0.001 to 0.100%, Hf: 0.001 to 0.100%, and REM: 0.001 to 0.100% The zinc-based plated steel sheet according to any one of (1) to (4), having a component composition containing one or more of the above. (6) The zinc-based plated steel sheet is a galvannealed steel sheet, the zinc-based plated layer has a composition containing 5 to 15% Fe and 0.01 to 1% Al, with the balance being Zn and impurities, and the coating weight of the zinc-based plated layer per one side is 10 to 100 g / m 2 The zinc-based plated steel sheet according to any one of (1) to (5), Effect of the Invention
[0013] According to the present invention, a zinc-based plated steel sheet having a thickness of 0.10 to 0.95 mm that can achieve both sufficient strength and plating properties can be provided, and a thin, high-strength zinc-based plated steel sheet with excellent appearance properties can be obtained. [Brief description of the drawings]
[0014] [Figure 1]FIG. 2 is a diagram for explaining a method for measuring the thickness of an internal oxide layer in the present invention. [Diagram 2] FIG. 2 is a diagram for explaining a method for measuring the thickness of a decarburized layer in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] For example, zinc-based plated steel sheets used for automotive parts are generally manufactured by hot rolling and cold rolling a steel piece having a predetermined composition of C, Si, Mn, etc., followed by annealing, followed by zinc-based plating treatment, and further alloying treatment as necessary. In the annealing before the zinc-based plating treatment, in order to form a zinc-based plating layer without unplated parts and / or to reduce alloying unevenness (unevenness in appearance after alloying treatment), it is preferable to appropriately control the annealing conditions to form an internal oxide layer containing oxides of Si, Mn, Al, etc. in the surface layer (i.e., inside) of the steel sheet. By forming the oxide inside the steel sheet, mutual diffusion between steel components (e.g. Fe) and plating components (e.g. Zn) occurs well in the zinc-based plating treatment, a zinc-based plating layer is well formed without unplated parts, and alloying unevenness during alloying can be reduced, improving plating properties. As a result, a zinc-based plated steel sheet with excellent appearance properties can be obtained. Therefore, in order to ensure sufficient plating properties in zinc-based plated steel sheets, it is effective to control the annealing conditions to form an internal oxide layer in the surface layer of the steel sheet.
[0016] On the other hand, when annealing is performed under annealing conditions that form an internal oxidation layer, a decarburized layer is usually formed near the surface of the steel sheet. Since the decarburized layer lacks carbon, which contributes greatly to the strength of the steel sheet, the presence of the decarburized layer reduces the strength near the surface of the steel sheet. When a zinc-based plated steel sheet is used for a member having a relatively thick plate thickness, the effect of the reduction in strength due to the decarburized layer is not large. However, in a member having a thin plate thickness, for example, a zinc-based plated steel sheet used for an automobile member such as a door, a bonnet, or a roof, the effect of the reduction in strength due to the decarburized layer is large, and it is extremely important to control the thickness of the decarburized layer. Therefore, in a zinc-based plated steel sheet having a plate thickness of 0.10 to 0.95 mm, which is less than 1 mm, it is preferable to achieve both the formation of an internal oxidation layer from the viewpoint of obtaining good plating properties (appearance properties) and the thinning of the decarburized layer from the viewpoint of ensuring strength.
[0017] Therefore, the present inventors have conducted various studies to achieve both high strength and high plating property in a zinc-based plated steel sheet having a thickness of 0.10 to 0.95 mm, and have found that it is effective to add a predetermined amount or more of C, Mn, Si, and Al to the steel, and further strictly control the ratio of the thickness of the internal oxide layer to the thickness of the decarburized layer on the surface of the steel sheet, and the ratio of the thickness of the decarburized layer to the sheet thickness of the steel sheet. More specifically, the present inventors have found that, in order to ensure plating property and strength, it is important to set A / B in the range of 0.01 to 0.50 and B / t in the range of 0.001 to 0.200, where A (μm) is the thickness of the internal oxide layer per side of the steel sheet, B (μm) is the thickness of the decarburized layer per side of the steel sheet, and t (μm) is the sheet thickness of the steel sheet.
[0018] <Zinc-plated steel sheet> Hereinafter, the zinc-based plated steel sheet according to the present invention (hereinafter, sometimes simply referred to as "plated steel sheet") will be described in detail.
[0019] The zinc-based plated steel sheet according to the present invention has a steel sheet and a zinc-based plated layer formed on at least one side of the steel sheet. Thus, the zinc-based plated layer may be formed on one side or both sides of the steel sheet. In the present invention, the zinc-based plated layer only needs to be formed on the steel sheet, and another plated layer may be provided between the steel sheet and the zinc-based plated layer. As described later, the zinc-based plated layer refers to a plated layer containing zinc, such as a hot-dip galvanized layer and an alloyed hot-dip galvanized layer.
[0020] [Steel plate] (composition) The composition of the steel sheet according to the present invention will be described. Unless otherwise specified, "%" regarding the content of an element means "mass%". In the numerical range of the composition, a numerical range expressed using "~" means a range including the numerical values written before and after "~" as the lower and upper limits, unless otherwise specified.
[0021] (C: 0.05~0.30%) C (carbon) is an important element for ensuring the strength of a zinc-based plated steel sheet. If the C content is insufficient, sufficient strength may not be ensured. Therefore, the C content is 0.05% or more, preferably 0.07% or more, more preferably 0.08% or more, and even more preferably 0.10% or more. On the other hand, if the C content is excessive, the strength may become excessively high, and the weldability may decrease. Therefore, the C content is 0.30% or less, preferably 0.25% or less, and more preferably 0.20% or less.
[0022] (Si: 0.01 to 3.00%) Si (silicon) is an element effective for improving the strength of steel sheet. In addition, Si is one of the elements that combine with oxygen during annealing to form internal oxides. On the other hand, Si is also an element that affects plating properties and alloying speed. If the Si content is insufficient, internal oxidation may not be generated sufficiently. Therefore, the Si content is 0.01% or more, preferably 0.03% or more or 0.05% or more, more preferably 0.10% or more or 0.30% or more. On the other hand, if the Si content is excessive, it may cause deterioration of the surface properties and lead to poor appearance. In addition, there is a risk that a Si-based oxide film (external oxide layer) may be generated on the steel sheet surface. Therefore, the Si content is 3.00% or less, preferably 2.50% or less, more preferably 2.00% or less.
[0023] (Mn: 0.80~3.00%) Mn (manganese) is an element effective in improving the strength of steel sheet by obtaining a hard structure. Mn is also one of the elements that combine with oxygen to form internal oxides during annealing. If the Mn content is insufficient, sufficient strength may not be ensured. Therefore, the Mn content is 0.80% or more, preferably 1.00% or more, and more preferably 1.20% or more. On the other hand, if Mn is added excessively, the metal structure may become non-uniform due to Mn segregation, and the workability may decrease. Therefore, the Mn content is 3.00% or less, preferably 2.80% or less, and more preferably 2.50% or less.
[0024] (Si+Mn: 5.00% or less, and Si / Mn: 1.50 or less) In the composition of the steel sheet according to the present invention, from the viewpoint of suppressing the formation of an outer oxide layer and promoting the formation of an inner oxide layer, the sum of the Si content and the Mn content (Si+Mn) is preferably 5.00% or less, more preferably 4.80% or less, and even more preferably 4.50% or less. The lower limit of Si+Mn is not particularly limited, but for example, Si+Mn may be 0.81% or more, 0.90% or more, 1.00% or more, or 1.20% or more. In addition, from the viewpoint of improving the appearance of the zinc-based plated steel sheet, the ratio of the Si content to the Mn content (Si / Mn) is preferably 1.50 or less, more preferably 1.20 or less. While Si and Mn contribute to improving the strength of the steel, excessive content of them may deteriorate the appearance, and the effect of Si on the appearance is more significant than that of Mn. Therefore, from the viewpoint of strength and the formation of inner oxides, by containing Si and Mn in a predetermined amount or more and lowering Si / Mn, the appearance can be maintained better. The lower limit of Si / Mn is not particularly limited, but may be, for example, Si / Mn is 0.01 or more, 0.03 or more, or 0.10 or more. Although Al can be substituted for Si, when Al is added as a substitute for Si, it is not necessary to take the Al content into consideration in the above sum and ratio.
[0025] (Al: 0.010~2.000%) Al (aluminum) is an element that acts as a deoxidizing element. If the Al content is less than 0.010%, the deoxidizing effect may not be sufficiently obtained. Therefore, the Al content is 0.010% or more, preferably 0.100% or more, and more preferably 0.200% or more. On the other hand, excessive Al content may cause a decrease in workability and deterioration of surface properties. Therefore, the Al content is 2.000% or less, preferably 1.500% or less, and more preferably 1.000% or less.
[0026] (P:0.100% or less) P (phosphorus) is an impurity generally contained in steel. If the P content exceeds 0.100%, the weldability may be reduced. Therefore, the P content is 0.100% or less, preferably 0.080% or less, more preferably 0.050% or less, and further preferably 0.020% or less. The lower limit of the P content is not particularly limited, but from the viewpoint of manufacturing costs, the P content may be more than 0% or 0.001% or more.
[0027] (S:0.100% or less) S (sulfur) is an impurity generally contained in steel. If the S content exceeds 0.100%, the weldability is reduced, and furthermore, the amount of MnS precipitated increases, which may reduce workability such as bendability. Therefore, the S content is 0.100% or less, preferably 0.080% or less, more preferably 0.050% or less, and further preferably 0.020% or less. The lower limit of the S content is not particularly limited, but from the viewpoint of desulfurization costs, the S content may be more than 0% or 0.001% or more.
[0028] (N:0.0300% or less) N (nitrogen) is an impurity generally contained in steel. If the N content exceeds 0.0300%, the weldability may be reduced. Therefore, the N content is 0.0300% or less, preferably 0.0200% or less, more preferably 0.0100% or less, and further preferably 0.0050% or less. There is no particular lower limit for the N content, but from the viewpoint of manufacturing costs, the N content may be more than 0% or 0.0010% or more.
[0029] (O: 0.010% or less) O (oxygen) is an impurity generally contained in steel. If the O content exceeds 0.010%, there is a risk of deterioration of ductility. Therefore, the O content is 0.010% or less, preferably 0.008% or less, more preferably 0.006% or less, and further preferably 0.005% or less. There is no particular lower limit for the O content, but from the viewpoint of production costs, the O content may be more than 0% or 0.001% or more.
[0030] In addition to the elements described above, the steel sheet of the present invention may contain optional elements described below as necessary.
[0031] (B: 0~0.0100%) Since B (boron) is an element that improves hardenability and contributes to improving strength, and also segregates at grain boundaries to strengthen the grain boundaries and improve toughness, it may be contained as necessary. Therefore, the B content is 0% or more, preferably 0.0001% or more, more preferably 0.0010% or more, and even more preferably 0.0020% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the B content is 0.0100% or less, preferably 0.0090% or less, and more preferably 0.0080% or less.
[0032] (Ti: 0~0.100%) Ti (titanium) is an element that precipitates as TiC during cooling of steel and contributes to improving strength, so it may be contained as necessary. Therefore, the Ti content is 0% or more, preferably 0.001% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. On the other hand, if it is contained excessively, coarse TiN may be generated and toughness may be impaired, so the Ti content is 0.100% or less, preferably 0.090% or less, and more preferably 0.080% or less.
[0033] (Nb: 0~0.100%) Nb (niobium) is an element that forms NbC in steel and has the effect of refining crystal grains, which contributes to improving strength, so it may be contained as necessary. Therefore, the Nb content is 0% or more, preferably 0.001% or more, more preferably 0.010% or more, and even more preferably 0.020% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the Nb content is 0.100% or less, preferably 0.090% or less, and more preferably 0.080% or less.
[0034] (V:0~0.10%) V (vanadium) is an element that forms VC and contributes to improving strength, so it may be contained as necessary. Therefore, the V content is 0% or more, preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.03% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the V content is 0.10% or less, preferably 0.09% or less, and more preferably 0.08% or less.
[0035] (Cr:0~1.00%) Cr (chromium) is an element that contributes to improving the strength and corrosion resistance of steel, so it may be contained as necessary. Therefore, the Cr content is 0% or more, preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.10% or more. On the other hand, if it is contained excessively, a large amount of Cr carbide is formed, which may adversely impair hardenability, so the Cr content is 1.00% or less, preferably 0.90% or less, more preferably 0.80% or less, and even more preferably 0.60% or less.
[0036] (Ni: 0~0.10%) Ni (nickel) is an element that contributes to improving the strength and corrosion resistance of steel, so it may be contained as necessary. Therefore, the Ni content is 0% or more, preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, from the viewpoint of production costs, etc., the Ni content is 0.10% or less, preferably 0.08% or less.
[0037] (Cu: 0~0.10%) Cu (copper) is an element that contributes to improving the strength and corrosion resistance of steel, so it may be contained as necessary. Therefore, the Cu content is 0% or more, preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, from the viewpoint of suppressing a decrease in toughness, cracking of the slab after casting, and a decrease in weldability, the Cu content is 0.10% or less, preferably 0.08% or less.
[0038] (Mo: 0~0.50%) Mo (molybdenum) is an element that contributes to improving the strength and corrosion resistance of steel, so it may be contained as necessary. Therefore, the Mo content is 0% or more, preferably 0.01% or more, and more preferably 0.10% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the Mo content is 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.
[0039] (W:0~0.50%) W (tungsten) is effective in increasing the strength of steel, so it may be contained as necessary. Therefore, the W content is 0% or more, preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.10% or more. On the other hand, from the viewpoint of suppressing the deterioration of toughness and weldability, the W content is 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.
[0040] (Ca: 0~0.100%) Ca (calcium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Ca content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, even more preferably 0.010% or more, and even more preferably 0.020% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Ca content is 0.100% or less, preferably 0.080% or less, and more preferably 0.050% or less.
[0041] (Mg: 0~0.100%) Mg (magnesium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Mg content is 0% or more, preferably 0.001% or more, more preferably 0.003% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Mg content is 0.100% or less, preferably 0.090% or less, and more preferably 0.080% or less.
[0042] (Zr: 0~0.100%) Zr (zirconium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Zr content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Zr content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less.
[0043] (Hf:0~0.100%) Hf (hafnium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Hf content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Hf content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less.
[0044] (REM:0~0.100%) REM (rare earth elements) are elements that contribute to inclusion control, particularly to finely dispersing inclusions, and have the effect of increasing toughness, and may be contained as necessary. Therefore, the REM content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if contained excessively, deterioration of surface properties may become apparent, so the REM content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less. REM is an abbreviation for Rare Earth Metal, and refers to elements belonging to the lanthanoid series. REM is usually added as misch metal.
[0045] In the present invention, the steel sheet may contain one or more of the following optional elements: B: 0.0001-0.0100%, Ti: 0.001-0.100%, Nb: 0.001-0.100%, Cr: 0.01-1.00%, Mo: 0.01-0.50%, and W: 0.01-0.50%. Alternatively or additionally, the steel sheet may contain one or more of V: 0.01-0.10%, Ni: 0.01-0.10%, Cu: 0.01-0.10%, Ca: 0.001-0.100%, Mg: 0.001-0.100%, Zr: 0.001-0.100%, Hf: 0.001-0.100%, and REM: 0.001-0.100%.
[0046] The balance of the steel sheet of the present invention other than the above-mentioned chemical composition consists of Fe and impurities. Here, the impurities refer to components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, during industrial production of the steel sheet, and are allowed to be contained within a range that does not adversely affect the properties of the zinc-based plated steel sheet of the present invention.
[0047] The analysis of the composition of the steel sheet may be carried out by any chemical analysis known to those skilled in the art, for example, by inductively coupled plasma mass spectrometry (ICP-MS). However, C and S may be measured using a combustion-infrared absorption method, and N may be measured using an inert gas fusion-thermal conductivity method. These analyses may be carried out on samples taken from the steel sheet by a method conforming to JIS G0417:1999.
[0048] (Thickness and width of steel plate) The present invention is directed to a zinc-based plated steel sheet using a steel sheet having a thickness of 0.10 to 0.95 mm. More specifically, the present invention is directed to a zinc-based plated steel sheet using a steel sheet having a thickness of 0.10 to 0.95 mm, which can be suitably used for components such as doors, bonnets, or roofs of automobiles. The thickness of the steel sheet is preferably 0.20 mm or more, more preferably 0.30 mm or more, from the viewpoint of ensuring strength. From the viewpoint of weight reduction, the thickness is preferably thin, and is preferably 0.70 mm or less, more preferably 0.60 mm or less, and further preferably 0.50 mm or less. Furthermore, since the zinc-based plated steel sheet according to the present invention is suitably used for automobile components such as doors, bonnets, or roofs, the width of the zinc-based plated steel sheet (i.e., steel sheet) is typically 1000 mm or more, and in some cases 1500 mm or more. The thickness of the steel sheet may be measured using a micrometer or the like. When measuring the thickness of a plated steel sheet excluding the plating layer, the thickness can be measured by removing the plating layer and measuring with a micrometer or the like, or by observing the cross section. The width of the steel sheet can be measured directly with a tape measure or measuring tape.
[0049] (internal oxide layer) The zinc-based plated steel sheet according to the present invention has an internal oxide layer containing oxides on the surface layer of the steel sheet (inside the steel sheet). The oxides in the internal oxide layer contain one or more of the elements contained in the steel sheet described above in addition to oxygen, and typically have a composition containing Si, O, Fe, and Mn, and further, in some cases, Al. Typically, the oxides have compositions such as Mn2SiO4, SiO2, and MnO. In the zinc-based plated steel sheet according to the present invention, an external oxide layer, i.e., an oxide layer in the form of a film on the surface of the steel sheet, is not formed, but an internal oxide layer, i.e., a layer in which oxides exist inside the steel sheet, is formed. Therefore, when a plating layer is formed, mutual diffusion between the steel components (e.g., Fe) and the plating components (e.g., Zn) occurs well, and the zinc-based plating is formed well on the steel sheet, and no unplated parts are formed, and a zinc-based plated steel sheet having excellent appearance properties can be obtained. In addition, when alloying treatment is performed, alloying unevenness can be suppressed, and a zinc-based plated steel sheet having excellent appearance properties can be obtained. In order to ensure plating properties, it is sufficient that a certain amount of the internal oxide layer is formed. Rather, if the internal oxide layer is formed thick, the decarburized layer, which is a factor of strength reduction, also becomes thick, so it is not preferable to form the internal oxide layer excessively. For example, the thickness of the internal oxide layer per side may be about 0.01 to 0.20 times the sheet thickness of the steel sheet. The thickness of the internal oxide layer per side of the steel sheet in the present invention: A (μm) is not particularly limited, but may be, for example, 1.0 μm or more, 2.0 μm or more, 3.0 μm or more, or 5.0 μm or more. The upper limit of A is not particularly limited, but from the viewpoint of suppressing the excessive formation of the decarburized layer, it may be, for example, 50.0 μm or less, 40.0 μm or less, 30.0 μm or less, or 20.0 μm or less.
[0050] (Decarburized layer) The zinc-based plated steel sheet according to the present invention has a decarburized layer near the surface of the steel sheet. The decarburized layer has a carbon concentration lower than that of the main part of the steel sheet (for example, the center of the sheet thickness). In the present invention, the decarburized layer refers to a region that is present on the steel sheet side from the interface between the steel sheet and the zinc-based plated layer, and has a lower carbon concentration than that in the base material. In addition, in the zinc-based plated steel sheet according to the present invention, as described later, the thickness of the decarburized layer relative to the sheet thickness of the steel sheet and the thickness of the internal oxidation layer is controlled, so that the decrease in strength of the zinc-based plated steel sheet due to the presence of the decarburized layer can be suppressed, and high strength can be achieved while ensuring plating properties. In the present invention, the thickness of the decarburized layer: B (μm) is preferably small from the viewpoint of ensuring higher strength. However, since the decarburized layer is formed to some extent together with the internal oxidation layer, B is not particularly limited, but is substantially 10 μm or more, and may be, for example, 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, or 40 μm or more. The upper limit of B is preferably 200 μm or less, more preferably 150 μm or less or 120 μm or less, and even more preferably 100 μm or less or 90 μm or less, from the viewpoint of ensuring a higher, particularly higher and more uniform strength.
[0051] (A / B:0.01~0.50) In the zinc-based plated steel sheet according to the present invention, it is necessary to promote the formation of an internal oxide layer in order to obtain high plating properties, while it is necessary to suppress the formation of a decarburized layer in order to obtain high strength. Therefore, it is preferable to reduce the thickness B (μm) of the decarburized layer per side while ensuring a certain degree of thickness A (μm) of the internal oxide layer per side. Therefore, in the present invention, the lower limit of A / B is set to 0.01. By setting A / B to 0.01 or more, both high strength and high plating properties can be achieved. If A / B is less than 0.01, the formation of the internal oxide layer is insufficient, resulting in a decrease in plating properties, and / or the decarburized layer becomes thick, resulting in insufficient strength. The lower limit of A / B is preferably 0.03 or 0.05, more preferably 0.10 or 0.15, and even more preferably 0.20. On the other hand, under conditions where internal oxidation usually occurs, the thickness B of the decarburized layer is thicker than the thickness A of the internal oxide layer, so the upper limit of A / B is substantially 0.50. The upper limit of A / B may be less than 0.50, 0.45, 0.40, or 0.30. From the viewpoint of ensuring strength, a thinner decarburized layer is preferable, but since some of the decarburized layer is formed when an internal oxide layer is formed to ensure plating properties, the thickness B of the decarburized layer per side in the present invention does not become 0. A means the thickness of the internal oxide layer per side of the steel sheet.
[0052] (B / t:0.001~0.200) Furthermore, in the zinc-based plated steel sheet according to the present invention, in order to suppress the formation of a decarburized layer and achieve high strength, it is preferable to make the thickness B (μm) of the decarburized layer per side smaller than the sheet thickness t (μm) of the steel sheet. In particular, since the sheet thickness of the steel sheet according to the present invention is very thin, 0.10 to 0.95 mm (100 to 950 μm), such control is extremely important. Therefore, in the present invention, the upper limit of B / t is set to 0.200. By making B / t 0.200 or less, the influence of strength reduction due to the presence of a decarburized layer can be suppressed, and a zinc-based plated steel sheet having sufficient strength can be obtained. If B / t exceeds 0.200, the decarburized layer becomes thicker than the sheet thickness of the steel sheet, and there is a risk that the strength will be insufficient. The upper limit of B / t may be 0.190, 0.180, 0.160, 0.140, 0.120, or 0.100. On the other hand, in the present invention, since it is necessary to form an internal oxide layer with a certain thickness to ensure plating properties, some decarburized layer is also formed. Therefore, the lower limit of B / t is substantially 0.001. The lower limit of B / t may be 0.010, 0.020, 0.030, 0.040, or 0.050. Note that B means the thickness of the decarburized layer per one side of the steel sheet. In other words, when B affects the strength of the steel sheet, both sides of the steel sheet are affected.
[0053] (Preferred embodiment when plate width is 1500 to 3000 mm) When a zinc-based plated steel sheet is used for an automobile member such as a door, a bonnet, or a roof, these members have a very large area, and therefore the zinc-based plated steel sheet may typically have a width of 1500 mm or more. According to a preferred embodiment of the present invention, in addition to controlling the ratio of the thickness of the internal oxidation layer to the thickness of the decarburized layer on the surface of the steel sheet and the ratio of the thickness of the decarburized layer to the sheet thickness of the steel sheet within a predetermined range as described above, the variation in the thicknesses of the internal oxidation layer and the decarburized layer in the width direction of the steel sheet can be strictly controlled, so that even in such a zinc-based plated steel sheet having a large sheet width and therefore a large area, good properties can be reliably achieved throughout the steel sheet. More specifically, in a zinc-based plated steel sheet having a thickness of 0.10 to 0.95 mm and a large width of 1500 to 3000 mm, the thickness of the internal oxide layer per one side of the steel sheet is A (μm), the thickness of the decarburized layer per one side of the steel sheet is B (μm), the standard deviation in the thickness of the internal oxide layer in the width direction is a (μm), and the standard deviation in the thickness of the decarburized layer in the width direction is b (μm). By controlling A to 1.0 μm or more, B to 10 μm or more, a / A to 0.15 or less, and b / B to 0.20 or less, it is possible to reliably achieve both high strength and high galvanizability in the entire steel sheet. In particular, according to the preferred embodiment of the present invention, the above-mentioned configuration allows the steel sheet to maintain high galvanizability and improve its appearance not only before forming but also after forming, i.e., after strain is applied. Hereinafter, the preferred embodiment of the present invention will be described in more detail.
[0054] (Steel plate width) The width of the steel plate may be 1500 to 3000 mm, for example, 1600 mm or more, 1800 mm or more, or 2000 mm or more. As described above, the width of the steel plate may be directly measured with a tape measure or a measuring tape.
[0055] (A: 1.0μm or more and a / A: 0.15 or less) In a preferred embodiment of the present invention, when the thickness of the internal oxide layer per one side of the steel sheet is A (μm) and the standard deviation of the thickness of the internal oxide layer in the width direction is a (μm), A is 1.0 μm or more and a / A is 0.15 or less. When a / A is 0.15 or less, the variation in the thickness of the internal oxide layer in the width direction of the steel sheet having a sheet width of 1500 to 3000 mm can be suppressed, and the thickness of the internal oxide layer can be controlled sufficiently uniformly over the entire steel sheet, and as a result, the zinc-based plated steel sheet according to the present invention can have high and uniform platability as a whole. On the other hand, if the value of a / A is too large, the thickness of the internal oxide layer over the entire steel sheet is not sufficiently uniform, the platability is not uniform in the width direction, and the zinc-based plated steel sheet may not have high and uniform platability as a whole. a / A is preferably 0.14 or less or 0.12 or less, more preferably 0.10 or less, and even more preferably 0.08 or less. The lower limit of a / A is not particularly limited, but since some variation in the thickness of the internal oxide layer occurs during manufacturing, a / A may be greater than 0 or greater than or equal to 0.01.
[0056] (B: 10μm or more and b / B: 0.20 or less) In a preferred embodiment of the present invention, when the thickness of the decarburized layer per one side of the steel plate is B (μm) and the standard deviation of the thickness of the decarburized layer in the width direction is b (μm), B is 10 μm or more and b / B is 0.20 or less. By making b / B 0.20 or less, the variation in the thickness of the decarburized layer in the width direction of the steel plate having a plate width of 1500 to 3000 mm can be suppressed. The uniformity of the decarburized layer in the width direction greatly affects the appearance when the outer panel is given a slight strain. That is, when local strength unevenness occurs under conditions where the steel plate is thin, the steel plate strength is high, and the decarburized layer thickness is relatively thick, the strain given from the outside may concentrate in the thick part of the decarburized layer, i.e., the part with low strength, causing local unevenness on the steel plate surface. In such a case, even if the steel plate has a good appearance before forming, the appearance unevenness in the L direction (rolling direction) may occur after the strain is given. By reducing b / B, localized unevenness in the material can be suppressed, and high plating properties can be maintained even after forming, ensuring a uniform appearance. b / B is preferably 0.15 or less, more preferably 0.12 or less, and even more preferably 0.10 or less. There is no particular lower limit for b / B, but since some variation in the thickness of the decarburized layer occurs during manufacturing, b / B may be greater than 0 or greater than 0.01.
[0057] (Measurement of the thickness of the internal oxide layer: A (μm) and calculation of the variation in thickness: a (μm)) The thickness of the internal oxide layer: A (μm) and the thickness variation: a (μm) are measured as follows. After the zinc-based plating layer of the zinc-based plated steel sheet to be measured is chemically dissolved and removed with a solution such as hydrochloric acid to which an inhibitor has been added, the composition in the thickness direction of the steel sheet is analyzed with a glow discharge optical emission surface analyzer (GDS) to evaluate the thickness of the internal oxide layer. Specifically, the sputtering depth after a certain period of sputtering from the surface of the steel sheet toward the thickness direction of the steel sheet is measured with a roughness meter, a laser microscope, or other method, and the sputtering rate per hour is calculated. Here, when Mn is internally oxidized, the concentration profile of Mn once decreases below the Mn signal intensity of the steel base, and then gradually increases to reach the Mn signal intensity of the steel base. In the present invention, the position where the Mn signal intensity reaches 0.9 times the Mn signal intensity of the steel base is defined as the internal oxidation position, and the sputtering time at which this internal oxidation position is reached is converted from the sputtering rate to thickness and is defined as the thickness of the internal oxidation layer. That is, in the present invention, the internal oxide layer refers to a region where the Mn concentration is 0.9 times or less of the Mn concentration of the steel substrate as measured by a glow discharge optical emission surface analyzer (GDS). FIG. 1 shows an example of a GDS profile of Mn, etc. The above operation is performed at three or more locations, and the thicknesses of the internal oxide layer obtained at each location are averaged to obtain the thickness A (μm) of the internal oxide layer per side in the present invention. In particular, in the case of a steel plate with a plate width of 1500 to 3000 mm, the thicknesses are measured at three locations in the width direction of the steel plate, namely, one end, the center, and the other end opposite to the one end, three locations at equal intervals between the one end and the center, and three locations at equal intervals between the center and the other end, for a total of nine locations, for a total of 18 locations on the front and back, and the thicknesses of the internal oxide layer obtained at each location are averaged to obtain the thickness A (μm) of the internal oxide layer per side in the present invention. In the present invention, the standard deviation a (μm) in the width direction of the thickness of the internal oxide layer is the standard deviation of the thickness of the internal oxide layer at 18 points obtained as described above. A high-frequency type GDS is used. In this specification, the measurement positions "one end" and "the other end" are positions 100 mm inward from the actual one end and the other end of the steel sheet, respectively.
[0058] (Measurement of the thickness of the decarburized layer: B (μm) and calculation of the variation in thickness: b (μm)) The measurement of the thickness of the decarburized layer: B (μm) and the calculation of the thickness variation: b (μm) are performed as follows. After the zinc-based plating layer of the zinc-based plated steel sheet to be measured is chemically dissolved and removed in a solution such as hydrochloric acid to which an inhibitor has been added, the thickness of the decarburized layer is evaluated by measuring the cross-sectional hardness distribution of the steel sheet. Specifically, the steel sheet is corroded with 2% nital to observe the steel sheet structure and estimate the thickness of the decarburized layer. Then, the Vickers hardness of the cross section is measured every 5 μm from the surface (interface between the steel sheet and the plating layer) toward the sheet thickness direction. In many cases, a measurement length of about 100 to 150 μm is sufficient for judgment. The thickness of the decarburized layer is defined as the position where the hardness distribution reaches the steel sheet hardness. That is, in the present invention, the "thickness of the decarburized layer" refers to the distance from the steel sheet surface to the hardness distribution by Vickers hardness reaches the steel sheet hardness. In this embodiment, the "hardness of the steel sheet" refers to the average value of the hardness measured at any 10 points in the center of the steel sheet in the thickness direction. An example of the actual measurement of the thickness of the decarburized layer is shown in FIG. 2. The load for the Vickers hardness is not particularly specified, but since the measurement is performed every 5 μm, it is desirable that the load is not too large. FIG. 2 shows the measurement at a load of 25 gf. The above operation is performed at three or more points, and the thicknesses of the decarburized layer measured at each point are averaged to obtain the thickness B (μm) of the decarburized layer per side in the present invention. In particular, in the case of a steel sheet with a sheet width of 1500 to 3000 mm, the thicknesses of the decarburized layer are measured at three points in the width direction of the steel sheet, namely, one end, the center, and the other end opposite to the one end, three points at equal intervals between the one end and the center, and three points at equal intervals between the center and the other end, for a total of nine points, for a total of 18 points on the front and back, and the thicknesses of the decarburized layer measured at each point are averaged to obtain the thickness B (μm) of the decarburized layer per side in the present invention. In the present invention, the standard deviation b (μm) in the width direction of the thickness of the decarburized layer is the standard deviation of the thicknesses of the decarburized layers at 18 locations obtained as described above.
[0059] (Tensile strength) The zinc-based plated steel sheet according to the present invention has a tensile strength of 550 to 1500 MPa. With a tensile strength of 550 MPa or more, sufficient strength can be ensured, and weight reduction can be achieved by thinning when used, for example, in automobile parts. The tensile strength is preferably 580 MPa or more or 600 MPa or more, more preferably 620 MPa or more, even more preferably 650 MPa or more, and most preferably 700 MPa or more. On the other hand, since there is a risk of reduced workability if the tensile strength is high, the tensile strength is set to 1500 MPa or less, and may be 1400 MPa or less or 1300 MPa or less. The tensile test is performed according to the method specified in JIS-Z2241:2011 using a JIS No. 5 tensile test piece, and the crosshead test speed of the tensile test is 30 mm / min. In particular, in the case of steel plates having a width of 1500 to 3000 mm, the tensile test is performed at three locations in the width direction of the steel plate, namely, one end, the center, and the other end opposite the one end, three locations at equal intervals between the one end and the center, and three locations at equal intervals between the center and the other end, for a total of nine locations, and the average value of the tensile strengths obtained at each location is regarded as the tensile strength according to the present invention.
[0060] [Zinc-based plating layer] The zinc-based plating layer in the present invention is formed on at least one side of the steel sheet. The term "zinc-based plating layer" typically refers to a plating layer whose main component (i.e., more than 50%) is Zn, but also includes a layer in which the components in the steel are diffused by performing heat treatment (e.g., alloying treatment) after plating, resulting in Zn being 50% or less. The zinc-based plating layer can be formed by various methods, but hot-dip galvanization is preferable. In addition, from the viewpoint of improving weldability and / or paintability, it is more preferable to perform alloying treatment after hot-dip galvanization. Therefore, the zinc-based plated steel sheet according to the present invention is preferably a hot-dip galvanized steel sheet, and more preferably an alloyed hot-dip galvanized steel sheet. In the present invention, since an internal oxide layer, not an external oxide layer, is formed on the surface layer of the steel sheet, the zinc-based plating layer can be formed, for example, in a state in which non-plated parts are suppressed, and when alloying treatment is performed, it can be formed in a state in which alloying unevenness is suppressed.
[0061] (Composition of zinc-based plating layer) A preferred composition of the zinc-based plating layer in the present invention will be described below. As long as the zinc-based plating layer is a plating layer containing Zn, the composition of the zinc-based plating layer is not particularly limited. Typically, the zinc-based plating layer contains 50 mass% or more of Zn. Hereinafter, "%" regarding the content of an element means "mass%" unless otherwise specified. In the numerical range of the composition, a numerical range expressed by "~" means a range including the numerical values written before and after "~" as the lower and upper limits, unless otherwise specified.
[0062] (Fe: 0-15%) When a Zn-containing plating layer is formed on a steel sheet and then the plated steel sheet is heat-treated, Fe can be contained in the plating layer by diffusing from the steel sheet. Therefore, the lower limit of the Fe content may be 0%. When an alloying treatment is performed to form a galvannealed layer, Fe in the steel diffuses into the plating layer, so in this case, the lower limit of the Fe content may be 1%, preferably 3%, and more preferably 5%. On the other hand, the upper limit of the Fe content may be 15%, preferably 12%, and more preferably 10%. Therefore, for example, when the zinc-based plating layer is a galvannealed layer, the Fe content in the plating layer may be 5 to 15%.
[0063] (Al: 0-30%) Since Al is an element that improves the corrosion resistance of the plating layer by being contained together with Zn or alloyed with Zn, it may be contained as necessary. Therefore, for example, when the plating layer is formed by electrolytic galvanization, the Al content may be 0%. In order to form a plating layer containing Zn and Al, the Al content is preferably 0.01% or more, for example, 0.1% or more, or 0.5% or more. On the other hand, since the effect of improving the corrosion resistance is saturated when it exceeds 30%, the Al content is preferably 30% or less, for example, 20% or less, 10% or less, 5% or less, or 1% or less. Even if the plating bath does not contain Al, when an alloying treatment is performed to form an alloyed hot-dip galvanized layer, Al in the steel diffuses into the plating layer. Therefore, in this case, for example, the Al content may be 0.01 to 1%.
[0064] The basic composition of the zinc-based coating layer is as described above. Furthermore, the zinc-based coating layer, particularly the galvannealed layer, may optionally contain the elements contained in the steel described above or other elements. These optional elements are not particularly limited, but from the viewpoint of fully exerting the action and function of the basic components constituting the coating layer, the total content is preferably 5% or less, more preferably 2% or less.
[0065] In the zinc-based plating layer of the present invention, the balance other than the above-mentioned composition is composed of Zn and impurities. Here, the impurities in the zinc-based plating layer mean components that are mixed in due to various factors in the manufacturing process, including raw materials, when the plating layer is manufactured, and are not components that are intentionally added to the plating layer. The plating layer may contain trace amounts of elements other than the basic components and optional components described above as impurities within a range that does not impair the effects of the present invention.
[0066] (Amount attached per side) The coating weight of the zinc-based plating layer in the present invention is not particularly limited, but is, for example, 10 to 100 g / m 2The coating weight per side has a large effect on corrosion resistance. From the viewpoint of corrosion resistance, the lower limit of the coating weight is preferably 15 g / m 2 , more preferably 20 g / m 2 , and more preferably 30 g / m 2 On the other hand, the upper limit of the coating amount per side is preferably 90 g / m from the viewpoints of formability, weldability, and economy. 2 , more preferably 70 g / m 2 , and more preferably 60 g / m 2 It would be good if that were the case.
[0067] The component composition and coating weight of the zinc-based plating layer can be determined by inductively coupled plasma (ICP) atomic emission spectrometry. Specifically, the component composition and coating weight of the zinc-based plating layer can be determined by dissolving only the zinc-based plating layer from a zinc-based plated steel sheet having the zinc-based plating layer and subjecting the resulting solution to ICP analysis. Note that the coating weight in the present invention is the amount per one side, so when a zinc-based plating layer is formed on both sides of a steel sheet, the coating weight on both sides is assumed to be the same in the calculation.
[0068] <Method of manufacturing zinc-based coated steel sheet> A preferred method for producing the zinc-based plated steel sheet according to the present invention will be described below. The following description is intended to exemplify a characteristic method for producing the zinc-based plated steel sheet according to the present invention, but is not intended to limit the zinc-based plated steel sheet to one produced by the method described below.
[0069] [Preparation of steel plates] The steel sheet in the present invention can be obtained by carrying out a casting process in which molten steel having an adjusted composition is cast to form a steel slab, a hot rolling process in which the steel slab is hot rolled to obtain a hot-rolled steel sheet, a pickling process in which the surface oxide (scale) and preferably the internal oxide layer formed in the hot rolling process are removed, a cold rolling process in which cold rolling is carried out to obtain a cold-rolled steel sheet, a grinding process in which the cold-rolled steel sheet is ground, and an annealing process in which the cold-rolled steel sheet is annealed.
[0070] (Casting process) The conditions of the casting process are not particularly limited. For example, after melting in a blast furnace or an electric furnace, various secondary smelting processes may be performed, and then casting may be performed by a method such as normal continuous casting, casting by an ingot method, or thin slab casting. Scrap may be used as the raw material, but the amount of scrap used is adjusted so that the content of each element in the resulting steel plate satisfies the above-mentioned range.
[0071] (Hot rolling process) The cast steel slab as described above can be hot-rolled to obtain a hot-rolled steel sheet. The hot rolling step is performed by hot-rolling the cast steel slab directly or after cooling it once and then reheating it. When reheating is performed, the heating temperature of the steel slab may be, for example, 1100°C to 1250°C. In the hot rolling step, rough rolling and finish rolling are usually performed. The temperature and rolling reduction of each rolling step may be appropriately determined according to the desired metal structure and plate thickness. For example, the finish rolling temperature may be 800 to 1050°C, and the finishing rolling reduction may be 50 to 80%. In the present invention, the thickness of the steel plate is finally reduced to 0.10 to 0.95 mm, so the load in the cold rolling step is large. For this reason, it is preferable to set the hot rolling reduction rate higher to make the plate thickness as small as possible during hot rolling, and specifically, it is preferable to make the plate thickness after hot rolling 2.5 mm or less. However, since the thickness of the internal oxidation layer and the decarburization layer formed near the surface of the steel sheet during hot rolling is almost constant, if the sheet thickness after hot rolling is reduced, the influence of the internal oxidation and decarburization during hot rolling becomes relatively large. On the other hand, if the internal oxidation layer and the decarburization layer formed during the hot rolling process are not sufficiently removed by the subsequent pickling process and grinding process and a relatively large amount of them remain, the internal oxidation layer and the decarburization layer during the annealing process are not formed well or are formed unevenly, which is undesirable. Therefore, in order to suppress the formation of the internal oxidation layer and the decarburization layer during the hot rolling process and to reduce the influence of the internal oxidation and decarburization during hot rolling, it is preferable to set the coiling temperature to 600°C or less, and more preferably to 550°C or less. In particular, when manufacturing a wide steel plate having a width of 1500 to 3000 mm, it is preferable to use a hot rolling lubricant having excellent lubricity as described in detail below, and to store the hot rolled coil after hot rolling and coiling with the inner diameter hole of the hot rolled coil lying horizontally (hole horizontal), thereby uniformly forming an internal oxide layer in the hot rolling process.
[0072] (Hot rolling lubricant) If the hot rolling lubrication conditions are not appropriate, the strain distribution on the surface of the steel sheet during hot rolling may be non-uniform. In such a case, the internal oxidation unevenness in the sheet width direction during hot rolling increases, which is also disadvantageous for the formation of a uniform internal oxidation layer and decarburized layer in the subsequent annealing process. Therefore, as the hot rolling lubricant for the hot rolling rolls, it is preferable to use a hot rolling lubricant with excellent lubricity, for example, a lubricant containing Ca sulfonate. By using such a hot rolling lubricant, the strain distribution on the surface of the steel sheet during hot rolling can be made uniform. Therefore, it is possible to significantly reduce the internal oxidation unevenness in the width direction during hot rolling.
[0073] (Hot rolled coils stored next to the hole) After hot rolling and winding, the hot rolled coil is temporarily stored until it is subjected to the subsequent pickling process and cold rolling process. In general, the hot rolled coil is stored with the inner diameter hole vertical (vertical hole) or horizontal (horizontal hole). However, if the hot rolled coil is stored with the hole vertical, the temperature variation in the sheet width direction increases, and internal oxidation unevenness in the sheet width direction may occur. In such a case, it is disadvantageous to the formation of a uniform internal oxidation layer and a decarburized layer in the subsequent annealing process. Therefore, in order to suppress or reduce such internal oxidation unevenness, it is preferable to store the hot rolled coil with the hole horizontal.
[0074] (pickling process) In order to remove the surface scale formed on the surface of the hot-rolled steel sheet during the hot-rolling process, a pickling process is carried out. In the pickling process, a hydrochloric acid-based solution is usually used, and the same conditions can be applied in the present invention. It is also desirable to remove the internal oxide layer formed during the hot-rolling process by the pickling process.
[0075] (cold rolling process) A cold-rolled steel sheet can be obtained by cold rolling a hot-rolled steel sheet. The reduction ratio of the cold rolling may be appropriately determined according to the desired metal structure and sheet thickness, and may be, for example, 30 to 90%. In the present invention, the reduction ratio of the hot rolling process and the reduction ratio of the cold rolling process may be appropriately adjusted to obtain a final desired sheet thickness, but since the sheet thickness of the steel sheet in the present invention is thin, less than 1 mm, for example, in order to prevent breakage in the cold rolling process, it is preferable to set the reduction ratio of the hot rolling larger than that of the cold rolling.
[0076] (Grinding process) It is preferable to carry out a grinding process in order to remove foreign matter remaining on the steel sheet surface, and further to remove the scale and internal oxide layer formed on the surface and surface layer of the steel sheet during hot rolling, as well as to uniformize the surface properties and promote the formation of the internal oxide layer in the next annealing process. More specifically, by carrying out the grinding process to sufficiently remove the internal oxide layer formed during hot rolling, and further imparting strain to the surface of the steel sheet, the diffusion of oxygen from the surface of the steel sheet to the inside in the annealing atmosphere is promoted, and the reaction with the oxygen is also activated, so that it is possible to promote the formation of the internal oxide layer in the annealing process. The grinding process is not particularly limited, but can be carried out by, for example, grinding the surface of the steel sheet using a heavy grinding brush. The desired surface roughness and grinding amount can be achieved by appropriately selecting the number, rotation speed, material, etc. of the heavy grinding brush. In particular, when manufacturing a wide steel sheet with a sheet width of 1500 to 3000 mm, the grinding process using multiple heavy grinding brushes can be carried out to uniformize the surface roughness over the entire steel sheet in the width direction, and strain can also be imparted uniformly over the entire steel sheet. Therefore, even for wide steel sheets, the reaction with oxygen in the annealing atmosphere is activated at every position on the steel sheet, making it possible to uniformly control the variation in thickness of the internal oxide layer and decarburized layer of the steel sheet. In particular, when manufacturing steel sheets with a width of 1500 to 3000 mm, it is preferable that the number of pairs of heavy grinding brushes arranged above and below the steel sheet is three or more (three pairs). This is because using a relatively large number of heavy grinding brushes to grind little by little is advantageous for uniforming the surface roughness over the entire steel sheet in the width direction and imparting uniform distortion. The total grinding amount of all heavy grinding brushes is 2 g / m per side.2 The grinding step can also be performed before the annealing and plating line described below.
[0077] (Annealing process) Next, the obtained cold-rolled steel sheet is annealed. The annealing is preferably performed at a temperature of 750°C or more, more preferably at a temperature of 780°C or more. The upper limit of the annealing temperature is preferably 920°C or less from the viewpoint of suppressing the formation of an outer oxide layer. The rate of temperature rise to the annealing temperature is not particularly limited, and may be, for example, 1 to 10°C / sec. In addition, from the viewpoint of sufficiently forming an inner oxide layer and suppressing the formation of an outer oxide layer, the holding time at the annealing temperature may be about 5 to 300 seconds, preferably 50 to 100 seconds. If the annealing time is too long, the decarburized layer may be formed in excess of the inner oxide layer, the B / t value may increase, and sufficient strength may not be obtained. The atmosphere in the annealing process is an important factor in controlling the inner oxide layer and the decarburized layer. It is possible to set the initial oxygen potential at a high oxygen potential and then reduce the oxygen potential, or it is possible to increase the oxygen potential throughout the entire annealing. The oxygen potential is determined by the water vapor partial pressure P in the annealing furnace. H2O Hydrogen partial pressure P H2 The common logarithm of the value divided by log(P H2O / P H2 ) and in order to obtain the internal oxide layer and the decarburized layer in the present invention, for example, the value obtained by the above formula can be controlled to -3.0 to -1.0. The method of increasing the oxygen potential can be a method of using a combustion atmosphere, adding a small amount of oxygen, increasing the dew point, or a combination of these. When controlling the dew point, the dew point is preferably -20°C or higher, and preferably -10°C or higher. If the dew point is too low, an outer oxide layer may be formed on the surface of the steel sheet. Although there is no particular upper limit for the dew point, in order to raise it above room temperature, it is necessary to take measures to suppress condensation. The atmosphere during annealing is preferably a reducing atmosphere, more preferably a reducing atmosphere containing nitrogen and hydrogen, for example, a reducing atmosphere containing 5% or less hydrogen (for example, 5% hydrogen and 95% nitrogen). The annealing process can be performed continuously with the formation of a zinc-based plating layer described later.
[0078] (Control of internal oxide layer thickness, decarburized layer thickness and their variation) As described above, the formation of the internal oxidation layer and the decarburization layer mainly depends on the conditions in the hot rolling process, the grinding process, and the annealing process. However, in addition to this, the thickness of the internal oxidation layer also depends on the amount of Si in the steel, and the thickness of the decarburization layer also depends on the amount of Si, Mn, and C in the steel. Increasing the amount of Si in the steel increases both the thickness of the internal oxidation layer and the thickness of the decarburization layer, and increasing the amount of Mn in the steel decreases the thickness of the decarburization layer. Similarly, increasing the amount of C in the steel decreases the thickness of the decarburization layer. Therefore, in order to increase A / B, it is effective to increase the amount of C and the amount of Mn. Also, as described above, when the thickness after hot rolling is reduced to 2.5 mm or less, the effects of internal oxidation and decarburization during hot rolling become relatively large. Therefore, it is important to suppress internal oxidation and decarburization during hot rolling by winding the steel sheet at a relatively low temperature in the hot rolling process, thereby reducing their effects. In addition, it is important to thoroughly remove the internal oxidation layer formed during hot rolling by the pickling process and the grinding process before the annealing process. In addition, the grinding process not only removes the internal oxide layer formed during hot rolling, but also applies strain to the steel sheet. The grinding process is a very important process because the application of strain to the steel sheet promotes the formation of the internal oxide layer in the subsequent annealing process. In addition, when manufacturing a wide steel sheet of 1500 mm or more in particular, it is necessary to appropriately select the hot rolling lubricant, the storage method of the hot rolled coil, and each condition of the grinding process from the viewpoint of controlling the variations a / A and b / B of the internal oxide layer thickness and the decarburized layer thickness in the width direction. Therefore, in order to make the values of A, B, A / B, B / t, a / A, and / or b / B appropriate, it is not enough to simply control the formation of the internal oxide layer and the decarburized layer in the annealing process, but it is also necessary to appropriately control each condition of the hot rolling process and the grinding process in addition to the amounts of Si, Mn, and C in the steel. The mutual influences of these conditions are complex and cannot be generalized; however, by fixing each condition to a certain extent, it is possible to appropriately control A, B, A / B, B / t, a / A, and b / B.In any case, the characteristics of the internal oxidation layer and the decarburized layer according to the present invention cannot be satisfied by simply combining the steel sheet composition, the hot rolling conditions, the grinding conditions, and the annealing conditions, and it is important to appropriately combine the steel sheet composition, the hot rolling conditions, the grinding conditions, and the annealing conditions so as to control these characteristics within the desired ranges.
[0079] [Formation of zinc-based plating layer] The zinc-based coating layer can be formed by either electrolytic galvanization or hot-dip galvanization, but is preferably formed by hot-dip galvanization. In the case of hot-dip galvanization, the conditions of the coating can be appropriately set in consideration of the desired component composition, thickness, and coating weight of the coating layer. For example, the cooling after annealing can be stopped at 430 to 500°C, and the cold-rolled steel sheet can be immersed in a coating bath of molten zinc for 1 to 5 seconds. The coating weight can be, for example, 10 to 100 g / m 2 That's fine.
[0080] After the formation of the zinc-based plating layer, it is preferable to carry out an alloying treatment in order to improve weldability and / or paintability. The alloying treatment conditions may be within the usual range, for example, the alloying treatment may be carried out at a temperature of 450 to 600°C. EXAMPLES
[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0082] (Example A: Manufacturing of zinc-based plated steel sheets) In this example, a zinc-plated steel sheet was manufactured by applying zinc-plating to a steel sheet having a thickness of 0.10 to 0.95 mm (100 to 950 μm) and a width of 1000 mm. First, molten steel with an adjusted composition was cast to form a steel billet, which was cooled once and then reheated and hot-rolled at a rolling reduction of 50% or more, and the resulting hot-rolled steel sheet was coiled. In all examples, the heating temperature of the steel billet during reheating was 1200°C, and the finish rolling temperature was 950°C. The sheet thickness and coiling temperature after hot rolling were as shown in Table 1. Then, pickling was performed using hydrochloric acid to remove surface scale until it was 0.2 μm or less. After pickling, cold rolling was performed at the cold rolling reduction shown in Table 1. Samples were taken from each cold-rolled steel sheet by a method conforming to JIS G0417:1999, and the composition of the steel sheet was analyzed. The thickness of each cold-rolled steel sheet was measured at five random locations using a micrometer, and the thicknesses were averaged to calculate the thickness t. The chemical composition and thickness of each steel sheet are shown in Tables 1 and 2.
[0083] Next, the surface of each cold rolled steel sheet was ground using a heavy grinding brush, and then annealed and hot-dip galvanized on a continuous plating line, and further alloyed except for No. 26. In Table 1, those that were alloyed after hot-dip galvanizing are indicated as "alloyed", and those that were not alloyed after hot-dip galvanizing are indicated as "molten zinc". The temperature, dew point, and holding time in annealing were as shown in Table 1, and the heating rate up to the annealing temperature was 10°C / sec. In addition, regarding the annealing atmosphere, Nos. 1 to 19, 21, 22, and 24 to 27 were annealed in a reducing atmosphere of 5% hydrogen and 95% nitrogen, using the formula: log(P H2O / P H2 The dew point was controlled so that the oxygen potential, calculated by the method described above, was -3.0 to -1.0. Nos. 20 and 23 were annealed at a low oxygen potential by controlling the dew point. For hot-dip galvanizing, the cooling after annealing was stopped at 480°C, and the cold-rolled steel sheet was immersed in a hot-dip galvanizing bath for 3 seconds, and the coating weight was adjusted to 50 g / m2 per side. 2The composition was adjusted to about 550° C. In each of Sample Nos. 101 to 125, 127, and 128, the hot-dip galvanizing was followed by an alloying treatment at 550° C. In all of the samples, the plating layer contained 5 to 15% Fe and 0.01 to 1% Al.
[0084] (Measurement of thickness A of the internal oxide layer) After chemically dissolving and removing the plating layer of each example with a hydrochloric acid solution containing an inhibitor, a high-frequency type GDS was used to analyze the composition of the steel sheet in the thickness direction and evaluate the thickness of the internal oxide layer. Specifically, the sputtering depth after a certain period of sputtering from the steel sheet surface toward the thickness direction of the steel sheet was measured with a laser microscope and the sputtering rate per hour was calculated. The position where the Mn signal intensity reached 0.9 times the Mn signal intensity of the steel base material was identified, and the sputtering time at this position was converted from the sputtering rate to a depth, which was determined as the thickness of the internal oxide layer. The above operation was performed at three locations, and the thicknesses determined at each location were averaged to obtain the thickness A (μm) of the internal oxide layer (per side).
[0085] (Measurement of the thickness B of the decarburized layer) The plating layer of each example was chemically dissolved and removed with a hydrochloric acid solution containing an inhibitor, and the thickness of the decarburized layer was evaluated by measuring the cross-sectional hardness distribution of the steel sheet. Specifically, the steel sheet was corroded with 2% nital to observe the steel sheet structure and estimate the thickness of the decarburized layer. Then, the Vickers hardness of the cross section was measured every 5 μm from the steel sheet surface (interface between the steel sheet and the plating layer) toward the sheet thickness direction. The measurement length was up to 100 μm. The position where the hardness distribution reached the steel sheet hardness was specified, and that position was regarded as the thickness of the decarburized layer. The above measurement was performed at three points, and the thickness of the decarburized layer was determined from the three data, and the thickness B (μm) of the decarburized layer (per side) in the present invention was obtained. The load when measuring the Vickers hardness was 25 gf.
[0086] (Evaluation of tensile strength) The tensile test was performed according to the method specified in JIS-Z2241:2011 using a JIS No. 5 tensile test piece. The crosshead test speed for the tensile test was 30 mm / min. The results are shown in Table 2.
[0087] (Evaluation of plating properties) The evaluation of the galvanizability was performed by evaluating the appearance of the zinc-based plated steel sheet of each example. Specifically, for the examples of alloyed hot-dip galvannealed steel sheets ("Alloyed" in Table 1), the appearance after alloying treatment was visually observed, with those in which no alloying unevenness was visible marked with ◎, those in which it was almost invisible marked with ○, and those in which it was visible or where the unplated area was visible marked with ×. For the examples of hot-dip galvannealed steel sheets ("Hot-dip zinc" in Table 1), the appearance after plating was visually observed, with those in which the unplated area was not visible marked with ◎, and those in which it was visible marked with ×. The results are shown in Table 2.
[0088] In this example, a zinc-based plated steel sheet having a tensile strength of 550 to 1500 MPa and a galvanizability rating of ⊚ or ◯ was evaluated as having sufficient strength and galvanizability.
[0089] [Table 1]
[0090] [Table 2]
[0091] Referring to Tables 1 and 2, in Example No. 104, the C content was excessive, so the strength of the steel sheet was too high and cold rolling was not possible, and an appropriate plate thickness could not be obtained. In Example No. 109, the C content was low, so the tensile strength was reduced. In Example No. 110, the Si content was excessive, which caused deterioration of the surface properties, and as a result, the galvanization properties were reduced. In Example No. 113, the Mn content was low, so the tensile strength was reduced. In Example No. 119, the Al content was excessive, which caused deterioration of the surface properties, and as a result, the galvanization properties were reduced. In Examples No. 120 and 123, the dew point during annealing was low, so the internal oxidation layer and decarburized layer were not formed, and sufficient galvanization properties were not obtained. In Example No. 127, the annealing time was long, so the decarburized layer was formed in excess of the internal oxidation layer, increasing B / t, and as a result, the tensile strength was reduced. In Example No. 128, the plate thickness after hot rolling was too thick, so the load in the cold rolling process was large, and an appropriate plate thickness could not be obtained. In contrast to this, in all examples according to the present invention, sufficient strength and galvanizability could be achieved by appropriately controlling the composition of the steel sheet, the ratio (A / B) of the thickness of the internal oxide layer on the steel sheet surface to the thickness of the decarburized layer, and the ratio (B / t) of the thickness of the decarburized layer to the sheet thickness of the steel sheet. In particular, extremely high galvanizability could be achieved in Examples Nos. 101 to 103, 105 to 108, 112, 114 to 118, 121, 122, and 124 to 126, in which the sum of the Si content and the Mn content (Si+Mn) was controlled to 5.00% or less and the ratio of the Si content to the Mn content (Si / Mn) was controlled to 1.50 or less.
[0092] (Example B: Manufacturing of wide zinc-based coated steel sheets) In this example, a zinc-plated steel sheet was manufactured by applying zinc-plating to a steel sheet having a thickness of 0.10 to 0.95 mm (100 to 950 μm) and a width of 1500 to 3000 mm. First, a molten steel having an adjusted composition was cast to form a steel billet, which was once cooled and then reheated, and hot-rolled at a rolling reduction of 50% or more using a Ca sulfonate-containing lubricant as a hot-rolling lubricant, and the obtained hot-rolled steel sheet was coiled, and the obtained hot-rolled coil was stored according to the storage method shown in Table 3. In all examples, the heating temperature of the steel billet during reheating was 1200°C, and the finish rolling temperature was 850°C. The use or non-use of a Ca sulfonate-containing lubricant, the thickness after hot rolling, and the coiling temperature were as shown in Table 3. Thereafter, the hot-rolled coil was pickled with hydrochloric acid to remove surface scale until it was 0.2 μm or less. After pickling, cold rolling was performed at the cold rolling reduction shown in Table 3. Samples were taken from each cold-rolled steel sheet in accordance with JIS G0417:1999, and the composition of the steel sheet was analyzed. The thickness of the steel sheet was measured at five random locations on the cold-rolled steel sheet using a micrometer, and the thickness was calculated by averaging the measurements. The width of the sheet was also measured using a tape measure. The composition, thickness and width of the steel sheet for each example are shown in Tables 3 and 4.
[0093] Next, for each cold-rolled steel sheet, the surface was ground in the grinding zone provided in front of the continuous plating line using the number of heavy-duty grinding brushes shown in Table 3 (the number of brushes when a pair of heavy-duty grinding brushes placed above and below the steel sheet is counted as one brush) at a total of 2 g / m per side for all heavy-duty brushes. 2 After grinding, the samples were annealed and hot-dip galvanized, and, except for No. 21, further alloyed. In Table 3, those that were alloyed after hot-dip galvanizing are indicated as "alloyed", and those that were not alloyed after hot-dip galvanizing are indicated as "molten zinc". The temperature, dew point, and holding time in annealing were as shown in Table 3, and the rate of heating up to the annealing temperature was 10°C / sec. The annealing atmosphere was a reducing atmosphere of 3% hydrogen and 97% nitrogen, and was calculated using the formula: log(P H2O / P H2The dew point was controlled so that the oxygen potential, calculated by the following formula, was kept between -3.0 and -1.0. For hot-dip galvanizing, the cooling after annealing was stopped at 480°C, and the cold-rolled steel sheet was immersed in a hot-dip galvanizing bath for 3 seconds, and the coating weight was kept at 50 g / m2 per side. 2 The composition was adjusted to about 550° C. In each of Sample Nos. 201 to 220 and 222 to 225, the plated layer was subjected to an alloying treatment at 550° C. after hot-dip galvanization. In all of the samples, the plated layer contained 5 to 15% Fe and 0.01 to 1% Al.
[0094] (Measurement of the thickness A of the internal oxide layer and calculation of the variation a (μm) of that thickness) After chemically dissolving and removing the coating layer of each example with a hydrochloric acid solution containing an inhibitor, a high-frequency type GDS was used to analyze the composition in the thickness direction of the steel sheet and evaluate the thickness of the internal oxide layer. Specifically, the sputtering depth after a certain period of sputtering from the surface of the steel sheet toward the thickness direction of the steel sheet was measured with a laser microscope, and the sputtering rate per hour was calculated. The position at which the Mn signal intensity reached 0.9 times the Mn signal intensity of the steel substrate was identified, and the sputtering time at this position was converted from the sputtering rate to a depth, which was defined as the thickness of the internal oxide layer. The above operation was performed at 9 points in the width direction of the steel sheet (center, 100 mm from both edges, and 3 points each dividing the edges and center into 4), for a total of 18 points on both sides, and the thicknesses obtained at each point were averaged to obtain the thickness A (μm) of the internal oxide layer (per side), and the standard deviation was calculated to obtain the standard deviation a (μm) of the thickness of the internal oxide layer in the width direction.
[0095] (Measurement of the thickness B of the decarburized layer and calculation of the variation b (μm) of that thickness) The plating layer of each example was chemically dissolved and removed with a hydrochloric acid solution containing an inhibitor, and the thickness of the decarburized layer was evaluated by measuring the cross-sectional hardness distribution of the steel sheet. Specifically, the steel sheet was corroded with 2% nital to observe the steel sheet structure and estimate the thickness of the decarburized layer. Then, the Vickers hardness of the cross section was measured every 5 μm from the steel sheet surface (interface between the steel sheet and the plating layer) toward the sheet thickness direction. The measurement length was up to 100 μm. The position where the hardness distribution reached the steel sheet hardness was identified, and that position was considered to be the thickness of the decarburized layer. As with the internal oxidation layer, measurements were taken at 9 points, a total of 18 points on both sides, and the average value and standard deviation were calculated to obtain the thickness B (μm) of the decarburized layer (per side) and the standard deviation b (μm) of the decarburized layer thickness in the width direction in the present invention. The load when measuring the Vickers hardness was 25 gf.
[0096] (Evaluation of tensile strength) The tensile test was performed using a JIS No. 5 tensile test piece according to the method specified in JIS-Z2241:2011. The crosshead test speed for the tensile test was 30 mm / min. The results are shown in Table 4. The tensile test was performed at nine points, similar to the internal oxidation layer, and the average value was taken as the tensile strength according to the present invention.
[0097] (Evaluation of plating properties) The plating property was evaluated according to the same criteria as in Example A.
[0098] (Evaluation of plating after applying 5% strain) For those that were rated as ◎ or ○ for plateability, samples were taken from the same positions as the tensile test pieces and evaluated for appearance after applying 5% strain by tension. Even if no unevenness in appearance was observed before tension, unevenness in appearance may occur after tension. Samples that showed no unevenness in appearance were rated as ○, and samples that showed unevenness in appearance were rated as ×.
[0099] In this example, similarly to Example A, zinc-based plated steel sheets having a tensile strength of 550 to 1500 MPa and plateability evaluation of ⊚ or ◯ (excluding evaluation of plateability after applying 5% strain) were evaluated as having sufficient strength and plateability.
[0100] [Table 3]
[0101] [Table 4]
[0102] Referring to Tables 3 and 4, in Example No. 201, the C content was low, which reduced the tensile strength. In Example No. 207, the Si content was high, which caused deterioration of the surface properties, resulting in reduced galvanizability. In Example No. 208, the Mn content was low, which reduced the tensile strength. In Example No. 211, the Al content was high, which caused deterioration of the surface properties, resulting in reduced galvanizability. In Example No. 225, the coiling temperature was high, which made it impossible to sufficiently suppress the formation of a decarburized layer during the hot rolling process, resulting in an increased B / t and reduced tensile strength.
[0103] In contrast, in all examples according to the present invention, sufficient strength and galvanizability could be achieved by appropriately controlling the composition of the steel sheet, the ratio (A / B) of the thickness of the internal oxide layer on the surface of the steel sheet to the thickness of the decarburized layer, and the ratio (B / t) of the thickness of the decarburized layer to the thickness of the steel sheet. In particular, in Examples 202-206, 209, 210, 212, and 215-222, in which the thickness (A) of the internal oxide layer on the surface of the steel sheet, the thickness (B) of the decarburized layer, and their variations in the width direction (a / A and b / B) were appropriately controlled in addition to the composition of the steel sheet, A / B, and B / t, no unevenness in appearance occurred even after 5% strain was applied, and therefore sufficient and uniform strength and galvanizability could be achieved throughout the steel sheet. In the other examples, i.e., Examples 213, 214, 223, and 224, although sufficient strength and galvanizability could be achieved, unevenness in appearance was observed after 5% strain was applied. Specifically, in Samples No. 213 and No. 214, the number of heavy-duty grinding brushes was small, which is believed to have resulted in insufficient uniformity of surface roughness and uniformity of strain across the entire steel sheet in the width direction, and as a result, the desired a / A and / or b / B were not obtained, and uneven appearance occurred after 5% strain was applied. In Sample No. 223, a / A and b / B were high because an appropriate hot rolling lubricant was not used in the hot rolling process, and as a result, uneven appearance occurred after 5% strain was applied. In Sample No. 224, the storage method of the hot-rolled coil after hot rolling and coiling was inappropriate, which resulted in high b / B, and as a result, uneven appearance occurred after 5% strain was applied. [Industrial Applicability]
[0104] Since the zinc-based plated steel sheet according to the present invention has sufficient plating properties and strength, it is possible to provide a high-strength zinc-based plated steel sheet having excellent appearance properties, and the zinc-based plated steel sheet can be suitably used for applications such as automobiles, home appliances, and building materials, particularly for automobiles. Therefore, the present invention can be said to be an invention of extremely high industrial value.
Claims
1. In mass percent, C: 0.05-0.30%, Si: 0.01-3.00%, Mn: 0.80-3.00%, Al: 0.010-2.000%, P: 0.100% or less, S: 0.100% or less, N: 0.0300% or less, O: 0.010% or less, B: 0 to 0.0100%, Ti: 0 to 0.100%, Nb: 0 to 0.100%, V: 0-0.10%, Cr: 0-1.00%, Ni: 0 to 0.10%, Cu: 0 to 0.10%, Mo: 0 to 0.50%, W: 0-0.50%, Ca: 0-0.100%, Mg: 0-0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0~0.100% and the balance being Fe and impurities, and the steel sheet has a sheet thickness of 0.10 to 0.95 mm; and a zinc-based plating layer formed on at least one surface of the steel sheet, The tensile strength is 550 to 1500 MPa, When the thickness of the internal oxide layer on one side of the steel plate is A (μm), the thickness of the decarburized layer on one side of the steel plate is B (μm), and the plate thickness of the steel plate is t (μm), A / B: 0.01 to 0.50, B / t: 0.001 to 0.200; When the sheet width of the steel sheet is 1500 to 3000 mm, the standard deviation in the width direction of the thickness of the internal oxidation layer is a (μm), and the standard deviation in the width direction of the thickness of the decarburized layer is b (μm), A: 1.0 μm or more, B: 10 μm or more; a / A: 0.15 or less, A zinc-based plated steel sheet having b / B of 0.20 or less.
2. The zinc-based plated steel sheet according to claim 1, wherein, in mass%, Si+Mn: 5.00% or less, and Si / Mn: 1.50 or less.
3. The steel plate comprises, in mass%, B: 0.0001 to 0.0100%, Ti: 0.001 to 0.100%, Nb: 0.001 to 0.100%, Cr: 0.01-1.00%, Mo: 0.01 to 0.50%, and W: 0.01~0.50% The zinc-based plated steel sheet according to claim 1 or 2, having a component composition containing one or more of the following:
4. The steel plate comprises, in mass%, V: 0.01-0.10%, Ni: 0.01 to 0.10%, Cu: 0.01 to 0.10%, Ca: 0.001-0.100%, Mg: 0.001-0.100%, Zr: 0.001 to 0.100%, Hf: 0.001 to 0.100%, and REM: 0.001~0.100% The zinc-based plated steel sheet according to any one of claims 1 to 3, having a component composition containing one or more of the following:
5. The zinc-based plated steel sheet is a galvannealed steel sheet, the zinc-based plated layer has a composition containing Fe: 5 to 15%, Al: 0.01 to 1%, and the balance being Zn and impurities, and the coating weight of the zinc-based plated layer per one side is 10 to 100 g / m 2 The zinc-based plated steel sheet according to any one of claims 1 to 4.
Citation Information
Patent Citations
Hot-dip galvannealed steel sheet and method for manufacturing the same
JP2010065269A
HIGH-Si-CONTAINING HOT-DIP GALVANNEALED STEEL SHEET SUPERIOR IN WELDABILITY AND MANUFACTURING METHOD THEREFOR
JP2011117041A
Hot-dip galvanized steel sheet and method of manufacturing the same
JP2012012655A
Hot dip galvannealed steel sheet excellent in productivity and press formability and production method thereof
JP2014058741A
Magnetic shield steel sheet and manufacturing method therefor
JP2017214617A